The Emerging Role(s) for Kisspeptin in Metabolism in Mammals - Wolfe, Andrew; Hussain, Mehboob A. (Frontiers in Endocrinology, 2018)
Kisspeptin was initially identified as a metastasis suppressor. Shortly after the initial discovery, a key physiologic role for kisspeptin emerged in the regulation of fertility, with kisspeptin acting as a neurotransmitter via the kisspeptin receptor (KISS1R), its cognate receptor, to regulate hypothalamic GnRH neurons, thereby affecting pituitary-gonadal function. Recent work has demonstrated a more expansive role for kisspeptin signaling in a variety of organ systems. Kisspeptin has been revealed as a significant player in regulating glucose homeostasis, feeding behavior, body composition as well as cardiac function. The direct impact of kisspeptin on peripheral metabolic tissues has only recently been recognized. Here we review the emerging endocrine role of kisspeptin in regulating metabolic function. Highlighted will be controversies and current limitations in the field as well as areas of future studies toward kisseptin’s diverse array of functions.